Opal and Ba/Ti ratio for IODP Holes 385-U1545A and 385-U1549A - Alejandro Aldama-Cervantes; Ligia Pérez-Cruz; Mauricio Velázquez-Aguilar; Jaime Urrutia-Fucugauchi; María Adela Monreal-Gómez; Martin Merino; Rafael Venegas-Ferrer; Joan Albert Sanchez-Cabeza; Abdelfettah Sifeddine; Tobias Walter Höfig (PANGAEA, 2025)
The dataset compiles paleoproductivity proxies from sediments recovered from the first 42.29 meters below the seafloor (mbsf) at Hole 385-U1545A, with a resolution of 30 cm for opal, Ba, Ti and Ba/Ti, and from the first 29.19 mbsf at Hole 385-U1549A, with a resolution of 60 cm for opal, Ba, Ti, and Ba/Ti. Sediment cores were obtained aboard the deep-sea vessel R/V JOIDES Resolution during International Ocean Discovery Program (IODP) Expedition 385 in the Guaymas Basin. The data includes Ages (cal yr BP), opal, Ba, Ti, Ba/Ti ratios, and opal difference between Site 385-U1545A and 385-U1549A.